FLIPPED CLASSROOM LEARNING STRATEGY FOR ENHANCEMENT OF BIOLOGY STUDENT ACADEMIC PERFORMANCE (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This review research paper aims to assess the effectiveness of the flipped classroom strategy  on student performance. The purpose is to analyze the impact of the flipped classroom model on academic achievement and explore its potential benefits in enhancing student learning outcomes. The study is grounded in the theoretical framework of constructivism and active learning. It investigates the flipped classroom strategy, which involves a reversal of traditional teaching methods, where students engage with instructional content outside the classroom through pre-recorded lectures or online resources, allowing for more interactive and collaborative activities during class time. A comprehensive literature review was conducted,utilizing both qualitative and quantitative research studies on the flipped classroom approach. The review encompasses a diverse range of academic disciplines and educational levels, providing a comprehensive analysis of the strategy's effectiveness in various contexts. The findings of this review indicate that the flipped classroom strategy has a positive impact on student performance. Students exposed to the flipped classroom model demonstrate improved academic achievement, increased engagement, enhanced critical thinking skills, and better retention of course content. Moreover, the flipped classroom   approach promotes active learning, collaboration, and self-directed learning, fostering a deeper understanding of the subject matter. The research findings have significant implications for educators, institutions, and policymakers. The adoption of the flipped classroom strategy can lead to pedagogical advancements, providing students with a more   personalized and engaging learning experience. The practical implications include the need for appropriate technology integration, professional development for educators, and the creation of supportive learning environments. From a social perspective, the flipped classroom approach has the potential to address educational inequalities, promote inclusivity, and prepare students for the demands of the 21st-century workforce. This review research paper contributes to the existing literature by providing a comprehensive synthesis of studies evaluating the effectiveness of the flipped classroom strategy. The paper highlights the value of the flipped classroom approach in enhancing student performance and sheds light on the theoretical underpinnings and practical implications associated with its implementation.